Забезпечення права на повагу до гідності осіб з обмеженими можливостями - Філіпська, Н. О.; Filipska, N. O.; Nataliia Filipska (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 1 (108), ч. 1. - С. 48-62, 2025)
Статтю присвячено дослідженню стану дотримання права на повагу до гідності осіб з обмеженими можливостями, особливо в умовах збройного конфлікту, воєнного стану та пов’язаних із цим викликів. Проаналізовано стан забезпечення права на повагу до гідності осіб з інвалідністю в Україні, зокрема в умовах збройного конфлікту. Виявлено системні порушення цього права. Особливу увагу приділено результатам дослідження, яке засвідчило низький рівень толерантності до осіб з обмеженими можливостями серед працівників правоохоронних органів. Обґрунтовано доцільність розроблення комплексу заходів, спрямованих на підвищення обізнаності суспільства, забезпечення доступності та соціальної інклюзії. Наголошено на необхідності системних змін у державній політиці з метою забезпечення повної реалізації прав осіб з інвалідністю, що стало б запорукою дотримання їхнього права на повагу до гідності.

The problem of ensuring the rights of persons with disabilities, in particular the right to respect for dignity, is one of the most acute in modern Ukrainian society. The article analyses this aspect in detail, focusing on the impact of the armed conflict and discriminatory practices on the lives of people with disabilities. Using the methods of synthesis and analysis, abstraction, induction, empirical and sociological, the author reveals that violations of the right to respect for the dignity of persons with disabilities are a systemic problem that manifests itself in various spheres of life: from limited access to infrastructure and social services to discrimination in labour relations and negative attitudes of society. Particular attention is paid to the problem of ensuring the security of this category of persons during military operations and the lack of training of law enforcement agencies to work with this category of population, which also affects the level of respect for dignity. It is concluded that the low level of perception of people with disabilities in Ukrainian society is a consequence of a set of social, cultural and historical factors that need to be overcome. The results of the author’s sociological research are presented, which show that there are stereotypes and prejudices against this category of persons among law enforcement officials. To address these problems, a set of measures is proposed, including: the introduction of an index of equality of persons with disabilities (this tool will allow to assess the level of inclusiveness of various spheres of life and develop targeted programmes to improve the situation); raising awareness of public authorities and society (conducting large-scale information campaigns aimed at forming a tolerant attitude towards people with disabilities); strengthening the role of civil society (support for the initiatives of NGOs). It is emphasised that ensuring the rights of persons with disabilities is not only a moral duty, but also an important factor for the development of society as a whole.
Ensuring the right to respect for the dignity of the persons with disabilities
Keywords: гідність; інвалідність; особи з обмеженими можливостями; особи з інвалідністю; права людини; доступність; інклюзивність; збройний конфлікт; соціальна політика; dignity; disability; persons with limited capacities; human rights; accessibility; inclusiveness; armed conflict; social policy